Acceptance of parents in behavior techniques management pharmacologic and nonpharmacologic in pediatric dentistry. (Aceptación de las técnicas de manejo farmacológicas y no farmacológicas en padres de pacientes pediátricos en odontología) - Cordero, Nicolás; Cárdenas, Juan Manuel; Álvarez, Luis Gonzalo (CES Odontología, 2013)
Introduction and Objective:The constant changes in the socio-cultural and ethical-legal conditions required to continually evaluatethe techniques of behavior management of pediatric patients in dental treatment. Identify the acceptanceof parents towards behavior management techniques used routinely in pediatric dentistry in a Colombianpopulation.Materials and Methods:A cross-sectional descriptive study was carried out in which 129 parents of children between ages 3and 15 evaluated a video which presented different behavior management techniques and completeda Questionnaire specifically designed for this study. Techniques evaluated include tell-show-do, positivereinforcement, contingent distraction, active immobilization, passive immobilization (papoose board),nitrous oxide sedation and general anesthesia.Results:Communicative techniques such as tell-show-do, positive reinforcement, modeling and contingentdistraction were significantly more accepted when compared with pharmacological techniques andrestrictive techniques were the least accepted. Conclusions:There is great rejection of parents to the traditional use of restrictive techniques and social trends requirethe dentist to use more communication techniques to manage the behavior of patients.Key words:Nitrous oxide sedation, General Anesthesia, Behavior Management, Pediatric Dentistry. Introducción y Objetivo:Los constantes cambios en el entorno socio-cultural y en las condiciones ético-legales exigen que seevalúen continuamente las técnicas de manejo de la conducta del paciente pediátrico. Identificar el nivelde aceptación que tienen los padres frente a las técnicas farmacológicas y no farmacológicas para elmanejo de la conducta en el tratamiento del paciente pediátrico en odontología.Materiales y métodos:Se hizo un estudio descriptivo transversal prospectivo en 129 padres de niños entre los 3 y 15 añosde edad, que evaluaron por medio de un cuestionario y un video las diferentes técnicas de manejode la conducta del paciente pediátrico: decir mostrar hacer, refuerzo positivo, modelado, distraccióncontingente, inmovilización activa y inmovilización pasiva (papoose board), sedación inhalada (oxidonitroso) y anestesia general.Resultados:Las técnicas comunicativas (Decir Mostrar Hacer, Refuerzo Positivo, Modelado, Distracción Contingente)fueron las más aceptadas al compararlas con las técnicas farmacológicas y las técnicas restrictivas fueronlas de menor aceptación.Conclusiones:Hay un gran rechazo de los padres hacia el uso tradicional de las técnicas restrictivas y las tendenciassociales actuales requieren que el odontólogo utilice más las técnicas comunicativas para el manejo delcomportamiento de los pacientes.Palabras clave:Oxido Nitroso, Anestesia General, Técnicas de manejo del comportamiento, Odontología Pediatrica.